The Aesthetic and Modernist Contrast in Nizar Qabbani’s Poem “أحبك في عصر لا يعرف ما هو الحب” from a Stylistic Perspective - As’ad, Zidan (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Modern Arabic poetry has evolved into a medium for ideological expression that transcends its purely aesthetic function. This article examines the stylistics of Nizar Qabbani’s poem titled أحبك في عصر لا يعرف ما هو الحب, focusing on the semantic level and the figurative level as analytical dimensions. This poem was selected because it explicitly juxtaposes pre-modern aesthetic values with the realities of modernity, thereby offering a productive field of study to assess how poetic language functions in responding to cultural change. This research applies the framework of contemporary Arabic stylistics developed by Qalyubi, as well as Al-Jadallah and Daraiseh, to identify the lexical and figurative strategies employed by the poet in semantic opposition. The findings reveal that lexical, temporal, and expressive oppositions in the semantic domain operate cumulatively to form an aesthetic tension that serves as the backbone of the poem, while imagery devices, including isti’arah murakkabah, takrir, kinayah, and muqabalah, function as ideological instruments that transcend mere aesthetic ornamentation. This study concludes that the entire stylistic system in this poetry operates along a coherent ideological line, namely, positioning love as a space of resistance against the logic of modernity that erodes the sacredness of human affective experience.